AWARENESS OF MEDICAL APPLICATIONS OF GINGKO BILOBA AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Herbal medicines reflect a significant portion of new interest in alternative therapies and Ginkgo biloba (GB) features significantly throughout this regard. The GB concentrate and any of its constituents is already thoroughly researched in terms of its impact on behavioral, physiological and psychological consequences linked with neurological and vascular conditions.The purpose of this survey was for assessing the awareness of medical applications of Gingko biloba amongst dental students. A cross sectional survey was conducted with a self-administered questionnaire with 10 queries circulated among 100 dental students. The questionnaire assessed the awareness about Ginkgo bilobatherapy in medical applications ,their anti dementia properties, anti alziemer properties,anti aging activity,anti inflammatory activity, and its mechanism of action and side effects. The responses were recorded and analysed.8% of the respondents were aware of the medical applications of Gingko biloba therapy.6 % were aware of the anti dementia activity of Gingko biloba therapy,5% were aware of anti alziemer properties of Gingko biloba therapy,6% were aware of anti aging properties of Gingko biloba therapy, 5% were aware of anti inflammatory properties of Gingko biloba therapy, 5% were aware mechanism of action and side effects of Gingko biloba therapy.The awareness about the usage of Ginkgo biloba therapy in medicinal applications is low among dental students.Increased awareness programs and sensitization and continuing dental education programs along with greater importance to the curricular modifications can further enhance knowledge and awareness about Ginkgo biloba therapy.